2010
DOI: 10.1097/psy.0b013e3181c2d6b8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Clinical Depression and Endothelial Function Measured by Forearm Hyperemic Reactivity

Abstract: Patients with clinical levels of depression had worse FHR than patients without depression, irrespective of CHD status and after adjusting for covariates. Data extend previous findings, suggesting that the link between clinical depression and worse CHD outcomes may be mediated by EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…4). In humans, endothelial dysfunction (2,3) was reported in patients with major depression, where impaired forearm flow-mediated vasodilatation was seen (8Y10, 33,39,40). In addition, reduced NO-dependent relaxation has been shown in studies of large arteries from rats (30,31) and mice (29,32) exposed to CMS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…4). In humans, endothelial dysfunction (2,3) was reported in patients with major depression, where impaired forearm flow-mediated vasodilatation was seen (8Y10, 33,39,40). In addition, reduced NO-dependent relaxation has been shown in studies of large arteries from rats (30,31) and mice (29,32) exposed to CMS.…”
Section: Discussionmentioning
confidence: 94%
“…Subgroups of anhedonic and resilient rats were randomly allocated to the various investigations (33,34). Two subgroups were assigned to the studies reported here, together with an unchallenged control group (control, n = 12; anhedonic, n = 12; resilient, n = 12).…”
Section: Methodsmentioning
confidence: 99%
“…Even a moderate increase in depressive symptoms is considered to affect endothelial dysfunction [19,20], which has also been observed in diabetic subjects with remitted major depressive disorder (MDD) [21]. Pathophysiological relationship of depression for the risk of CVD showed that in depressed patients, platelet aggregation is significantly enhanced with increased expression of glycoprotein-1b (Gp1B), fibrinogen, factor V and anionic phospholipids [22].…”
Section: Endothelial Dysfunctionmentioning
confidence: 98%
“…Studies investigating the association between depression and arteriosclerosis have used a variety of indexes for vascular function (Lavoie et al 2010;Oulis et al 2010;Paranthaman et al 2010;Rajagopalan et al 2001;Rybakowski et al 2006;Sherwood et al 2005;Tiemeier et al 2003). Irrespective of these different outcome measures, all studies unanimously have shown depressed individuals to have impaired endothelial function or increased arterial stiffness.…”
Section: Existing Evidence On Association Between Depression and Subcmentioning
confidence: 99%